Effects of ethrel, 1‐MCP and modified atmosphere packaging on the quality of 'Wonderful' pomegranates during cold storage. (10th May 2018) - Valdenegro, Mónika; Huidobro, Camila; Monsalve, Liliam; Bernales, Maricarmen; Fuentes, Lida; Simpson, Ricardo
Abstract: BACKGROUND: Pomegranate ( Punica granatum ) is a non‐climacteric fruit susceptible to chilling injury (CI) at temperatures below 5 °C. To understand the influences of ethylene and modified atmosphere on CI physiological disorders of pomegranate, exogenous ethrel (0.5, 1 and 1.5 µg L −1 ) treatments, 1‐methylcyclopropene (1‐MCP) (1 µL L −1 ) exposure, packaging in a modified atmosphere (MAP) (XTend™ bags; StePac, São Paulo, Brazil), a MAP/1‐MCP combination, and packaging in macro‐perforated bags (MPB) were applied. The treated fruits were cold stored (2 ± 1 °C; 85% relative humidity) and sampled during 120 + 3 days at 20 °C. RESULTS: During cold storage, CI symptoms started at 20 days in MPB and at 60 days for all exogenous ethylene treatments, and were delayed to 120 days in MAP, 1‐MCP and MAP/1‐MCP treatments. MPB and ethylene treatments induced significant electrolyte leakage, oxidative damage, lipid peroxidation, ethylene and CO2 production, and 1‐aminocyclopropane‐1‐carboxylic acid oxidase activity, without any change in total soluble solids, titratable acidity or skin and aril colours. Conversely, MAP by itself, or in combination with 1‐MCP application, effectively delayed CI symptoms. CONCLUSION: During long‐term cold storage of this non‐climacteric fruit, ethrel application induced endogenous ethylene biosynthesis, accelerating the appearance of CI symptoms in contrast to the observations made for MAP and 1‐MCP treatments. © 2018 Society of Chemical Industry